TINGKAT KEPUASAN PASIEN TERHADAP PELAYANAN KEFARMASIAN DI UPT PUSKESMAS BROMO KECAMATAN MEDAN DENAI - Hidayah, Nurul; Sitepu, Nadroh; Hilda, Hilda; Masniah, Masniah; Ulina, Kartika (Universitas Tadulako, 2023)
Patient satisfaction is an important part of pharmaceutical services and is one of the parameters of the quality of pharmaceutical services. The purpose of the study was to determine the level of patient satisfaction with pharmaceutical services at UPT Puskesmas Bromo, Medan District. This type of research is a descriptive survey. The research location is at UPT Bromo Public Health Center, Medan City. The sample in this study were 86 respondents who met the inclusion criteria. The data was collected by distributing service satisfaction questionnaires that included five dimensions, namely tangible, assurance, reliability, empathy, and responsiveness. The results showed that patient satisfaction based on tangible was 74.79% (Satisfied), assurance was 84.88% (Satisfied), reliability was 75.39% (Satisfied), empathy was 75.48% (Satisfied), and responsiveness (76.27% (Satisfied). It can be concluded that the average level of patient satisfaction is 76.74% (satisfied category) which indicates that the Pharmaceutical care at the Bromo Health Center UPT have been implemented according to pharmaceutical standards so as to provide a sense of satisfaction to patients who receive pharmaceutical care.